G-quadruplex DNA and RNA in cellular senescence - Diaz Escarcega, Rocio; Marshall, Paul; Tsvetkov, Andrey S. (Frontiers in Aging, 2024)
Normal cells divide, are damaged, and are repaired across their lifetime. As cells age, they enter cellular senescence, characterized by a permanent state of cell-cycle arrest triggered by various stressors. The molecular mechanisms that regulate senescent phenotypes have been actively investigated over the last several decades; however, one area that has been neglected is how G-quadruplex (G4) DNA and RNA (G4-DNA and G4-RNA) mediate senescence. These non-canonical four-stranded DNA and RNA structures regulate most normative DNA and RNA-dependent processes, such as transcription, replication, and translation, as well as pathogenic mechanisms, including genomic instability and abnormal stress granule function. This review also highlights the contribution of G4s to sex differences in age-associated diseases and emphasizes potential translational approaches to target senescence and anti-aging mechanisms through G4 manipulation.